2015
DOI: 10.1080/15459624.2014.987386
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Variation in Occupational Exposure to Air Contaminants

Abstract: Many industrial workers are exposed to air contaminants. A significant proportion of this exposure is found to occur as short peaks, a fact that has received limited attention in the literature. The present study focuses on short-term variation in air contaminant exposure measured at the level of seconds, linking exposure peaks to typical work situations in selected Swedish industries. The video exposure monitoring method was used to characterize this variation. Ten different videos were analyzed, from recordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the main survey, the OPA concentrations of the identified high‐concentration exposure processes measured by DNPH‐HPLC ranged from 1.18 to 4.49 ppb (Table 2). In the previous studies, the sampling duration for measuring the OPA concentration and the OPA concentration were reported as 5 minutes and 2.01 ppb, 3 3‐22 minutes and not detected (0.2 ppb) to 10.0 ppb, 4 and 10 minutes and not detected (3.0 ppb) to 10 ppb, 9 respectively. Although the OPA concentrations in this study were similar to those used in previous studies, it is considered that the results of the previous studies were due to the combination of some high‐concentration exposure processes because the endoscope washing procedures were carried out as diverse, consecutive, and short.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the main survey, the OPA concentrations of the identified high‐concentration exposure processes measured by DNPH‐HPLC ranged from 1.18 to 4.49 ppb (Table 2). In the previous studies, the sampling duration for measuring the OPA concentration and the OPA concentration were reported as 5 minutes and 2.01 ppb, 3 3‐22 minutes and not detected (0.2 ppb) to 10.0 ppb, 4 and 10 minutes and not detected (3.0 ppb) to 10 ppb, 9 respectively. Although the OPA concentrations in this study were similar to those used in previous studies, it is considered that the results of the previous studies were due to the combination of some high‐concentration exposure processes because the endoscope washing procedures were carried out as diverse, consecutive, and short.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, visual confirmation of the exposure level during his/her work becomes possible. VEM is used as an analysis tool for works involving exposure, to support training in communication of risks, and to promote participation and motivation of workers in improving the workplace environment 8,9 . In this study, as a new way of utilizing VEM, the high‐concentration exposure processes were identified using VEM to assess the ceiling values with high accuracy.…”
Section: Introductionmentioning
confidence: 99%